The Efforts of the Royal Thai Domestic Bureaucracy in an Effort to Protest against the Haze/Smog from Indonesia - Thaan Neet Bunprakop; Ong Argo Victoria; Firdo Lingga (Jurnal Daulat Hukum, 2023)
This study aims to explain three determinant factors in influencing a country in making policies, especially the kingdom of Thailand. The three determinants of the considerations above have an interconnected role in influencing every consideration of policy makers to make decisions. Where in the domestic context, which consists of domestic politics, economic and military forces play a role together with the international context in shaping the direction of foreign policy. So that these three considerations do not stand separately because they influence each other in the policy-making process. The existence of deforestation and fires in Indonesia has caused significant problems. Because deforestation and forest fires are directly transboundary haze which makes Indonesia a smoke haze contributing country in the Southeast Asian region. Therefore, in relation to forest fires in Indonesia which have become an environmental issue, the Indonesian government also has a responsibility towards cross-border air pollution. Where in terms of international law, state responsibility is an obligation that must be carried out by a country to other countries. So that the Indonesian government in this case has responsibility for cross-border air pollution that occurs in Southeast Asia. The Indonesian government has also ratified ASEAN Agreement on Transboundary haze pollution (AATHP). Therefore, the Indonesian government is trying to solve this problem in a sustainable manner.